Significant role of host sialylated glycans in the infection and spread of severe acute respiratory syndrome coronavirus 2 - Saso, Wakana; Yamasaki, Masako; Nakakita, Shin-ichi; Fukushi, Shuetsu; Tsuchimoto, Kana; Watanabe, Noriyuki; Sriwilaijaroen, Nongluk; Kanie, Osamu; Muramatsu, Masamichi; Takahashi, Yoshimasa; Matano, Tetsuro; Takeda, Makoto; et al. (PLoS pathogens, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been transmitted across all over the world, in contrast to the limited epidemic of genetically- and virologically-related SARS-CoV. However, the molecular basis explaining the difference in the virological characteristics among SARS-CoV-2 and SARS-CoV has been poorly defined. Here we identified that host sialoglycans play a significant role in the efficient spread of SARS-CoV-2 infection, while this was not the case with SARS-CoV. SARS-CoV-2 infection was significantly inhibited by α2-6-linked sialic acid-containing compounds, but not by α2–3 analog, in VeroE6/TMPRSS2 cells. The α2-6-linked compound bound to SARS-CoV-2 spike S1 subunit to competitively inhibit SARS-CoV-2 attachment to cells. Enzymatic removal of cell surface sialic acids impaired the interaction between SARS-CoV-2 spike and angiotensin-converting enzyme 2 (ACE2), and suppressed the efficient spread of SARS-CoV-2 infection over time, in contrast to its least effect on SARS-CoV spread. Our study provides a novel molecular basis of SARS-CoV-2 infection which illustrates the distinctive characteristics from SARS-CoV.